(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In Train to Pakistan, Khushwant Singh seeks to dramatize various nuances of violence unleashed by partition within the conceptual framework of sin and sacrifice. This is apparent from the way the whole narrative is constructed. In the very beginning of the novel, the author visualizes communal riots in terms of sin that is grounded in the disruption of the normal order. The moral–emotional charge inherent in the description tends to place this violence within a discourse that draws its language from both sacrifice and feud. It even touches the emotional chords in the readers. In contrast to the repulsive hooliganism of the Muslim marauders, it generates pathos.